READING IS A GUARANTEE OF A GREAT FUTURE (Scientific journal of the Fergana State University, 2024)
A book is an unquenchable light that illuminates the paths of life, a source of happiness that gives meaning to a personʼs life, a loyal friend that accompanies him in any situation. There is no tool as powerful as a book to ensure the spiritual maturity of a person. That is why, from time immemorial, leaders of enlightenment and wise people have invited all mankind to read books and learn the secrets of science and manners from them. Today, children are often accused of not reading. But parents, teachers, and librarians sometimes ignore the need to recommend colorful literature to them.